The risen : a novel - Rash, Ron, 1953- (Ecco, an imprint of HarperCollins Publishers, 2016)
Estranged for decades after a turbulent 1969 summer spent with a free-spirited redhead, two brothers are forced by a shocking reminder to confront the past events that divided them.